Research the Opportunities a Foreign Languages’ Competence for Professional Project Management in Latvia - Barbare, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the current competitive working environment time has become the key resource therefore universities must be able to satisfy higher education needs by enabling students to obtain as many professional skills and knowledge as possible. One of the solutions is to develop online studies by organising the language courses on the internet and by supplementing in-class courses with online study materials. The goal of this work is to research the opportunities a foreign languages’ competence for professional project management in Latvia. Research materials on foreign language teaching methods and applicable IC technological aspects were gathered, and a survey was completed and its results analysed to find out the opinions and attitude towards learning online from second foreign language students and people studying independently. During the work it was discovered that applying the new technologies positively influences the students’ willingness to study the foreign language independently. Focusing on students’ motivation on autonomous study style, online studies have a potential and opportunity to be applied and developed for higher education study program expansions.